Peptidomimetics as Potential Anti-Virulence Drugs Against Resistant Bacterial Pathogens - Martínez, Osmel Fleitas; Duque, Harry Morales; Franco, Octávio Luiz (Frontiers in Microbiology, 2022)
The uncontrollable spread of superbugs calls for new approaches in dealing with microbial-antibiotic resistance. Accordingly, the anti-virulence approach has arisen as an attractive unconventional strategy to face multidrug-resistant pathogens. As an emergent strategy, there is an imperative demand for discovery, design, and development of anti-virulence drugs. In this regard, peptidomimetic compounds could be a valuable source of anti-virulence drugs, since these molecules circumvent several shortcomings of natural peptide-based drugs like proteolytic instability, immunogenicity, toxicity, and low bioavailability. Some emerging evidence points to the feasibility of peptidomimetics to impair pathogen virulence. Consequently, in this review, we shed some light on the potential of peptidomimetics as anti-virulence drugs to overcome antibiotic resistance. Specifically, we address the anti-virulence activity of peptidomimetics against pathogens’ secretion systems, biofilms, and quorum-sensing systems.